Transforming the Quality of Tahfidz and Religious Programs Through Relational Leadership of Madrasah Principals - Zackyl Mustofa; Siti Khofsah; Annisa Tri Ananda Dewi; Moh. Holidi; Robert Edy Sudarwan (International Journal of Instructional Technology, 2026)
This study aims to analyze the implementation of relational leadership in improving the quality of tahfidz and religious programs in Islamic elementary schools. The research employs a qualitative case study approach to explore leadership practices, collaborative commitment building, and the transformation of program quality. Data were collected through interviews, observation, and documentation involving principals, teachers, and program supervisors, and analyzed using data condensation, data display, and verification techniques. The findings show that relational leadership is implemented through open communication, role modeling, and collaborative decision-making, which strengthens trust and engagement among school members. Shared commitment to program quality is built through teacher involvement in planning, implementation, and evaluation processes. The study also reveals that relational leadership contributes to improved student discipline, increased memorization achievement, and stronger motivation in religious learning activities. The implication of this study is that relational leadership serves as a key driver in transforming educational quality by fostering collaboration, trust, and sustainable commitment within the school environment, particularly in strengthening tahfidz and religious education programs.